Signs of expression - Bosy, Karen; Portugal, Cristina (InfoDesign, 2019)
This paper takes as a starting point McLuhan’s (1966) ideas of media as an extension of the self, and that technology extends natural human abilities. To discuss and reflect on these issues, we chose to conduct practical research through asking artists and designers to each produce a video as a personal/professional response to a specific prompt. This collaboration developed from a discussion initially centered around organising a series of interviews on the subject of media and specifically choice of media employed within a practice, and the ways in which this may contribute to meaning, creating interpretations of a resultant work. The decision to ask contributors to use moving image as a way to represent their own medium and way of working moved this project away from a text-based format. A series of videos was produced exploring a subjective discourse where one can perceive these media as an extension of the physical, or an environment where a language can be shared. In these works, the process of viewing, imagining, judging, and making meaning becomes reliant on active, reflexive, self-critical, construction of vision, through subjectivised experiences.